Utilization of the Internet of Things to Optimize Teaching Factory in Vocational Schools: Industry 5.0-Based Learning Innovation - Ratna Fajarwati Meditama; Aries Musnandar; Sutrisno Sutrisno; Irsyad Dzulfiqar Abidin; Andika Hariyanto Surbakti (Yayasan Adra Karima Hubbi, 2024)
Background. The Industrial Revolution 5.0 demands innovation in the education sector, particularly in Vocational High Schools (SMK), to prepare graduates capable of competing in the digital era and smart industry. This research explores the integration of the Internet of Things (IoT) within the Teaching Factory concept in SMK as a strategy to optimize industry-based learning. IoT technology enables the Teaching Factory to simulate real industrial environments, allowing students to be actively involved in production processes supported by real-time data and automation. Purpose. The purpose of this study is to analyze the benefits of IoT implementation in the Teaching Factory to enhance student readiness for the workforce. Method. The research method includes a literature review and a case study of SMKs that have integrated IoT into their Teaching Factory activities. Results. The results indicate that IoT use increases efficiency and productivity in the learning process while enriching students’ learning experiences through interactive and adaptive methods. IoT integration also helps students develop relevant skills for the workforce, thus reducing unemployment rates in Indonesia. Conclusion. In conclusion, the incorporation of IoT into the Teaching Factory concept offers significant opportunities for SMK to better prepare students for the challenges of Industry 5.0. This article provides practical recommendations for SMK administrators to develop IoT-based curricula and learning infrastructure to align with industrial needs.